Optimization of inter-plant water network design involving multiple contaminants - M. A. A., Azmi; M. N., Arifin; Zainatul Bahiyah, Handani (IOP Publishing, 2020)
Minimization of freshwater consumption and wastewater generation are being critical concerns in the process industry due to the scarcity in freshwater supply, the increase of freshwater and effluent treatment costs and stricter regulations. One of the efficient ways to reduce freshwater consumption in the process is by recycling and/or reusing wastewater that is generated by the process or utility after being treated to acceptable limits. This work presents the development of a systematic approach for synthesizing indirect inter-plant water network integration with centralized regeneration system involving multiple contaminants. In this approach, water reuse prospects were analysed within individual plants and between different plants via inter-plant water integration possibilities. The water network problem is formulated as a mixed integer nonlinear programming (MINLP) based on the water network superstructure and is solved using GAMS optimization software. The applicability of the proposed approach is illustrated using a wafer manufacturing process plants case study. At the end of this study, significant reductions of freshwater consumption and wastewater generation have been achieved, showing the effectiveness of the proposed approach. The results show that the freshwater consumption and wastewater generation reduced about 47.61% and 53.48% respectively.